Circadian variation in stroke: a hospital-based study - Kabir, Mohammed Ruhul; Hasan, A. B. M. Kamrul; Hasan, Mohammed Kamrul; Chakraborty, Shishir Ranjan; Rahman, Matiur (International Journal of Advances in Medicine, 2019)
Background: Proof of a circadian rhythm in the occurrence of cerebral infarction and other types of stroke might provide clues to factors which immediately precipitate these events, which in turn might lead to more rational treatments. The aims of the current study were to find out the circadian variation of stroke onset and to determine the risk factors related to circadian variation. Methods: This cross-sectional study was conducted in a tertiary hospital of Bangladesh from July to December 2014 among 67 diagnosed cases of ischemic and hemorrhagic stroke of first attack. Times of onset of stroke and wake-sleep state were recorded. Results: The mean age of the study subjects was 62.1 years, 64.2% were male. Among them, 59.7% had an ischemic stroke and 40.3% had a hemorrhagic stroke. The occurrence of stroke was most common during 6 am to 12 pm (47.8%), followed by 12 am to 6 am (25.4%), 12 pm to 6 pm (17.9%), and 6 pm to 12 am (9.0%). Circadian variation of stroke was homogenous and statistically insignificant in association with age group when categorized as below 65 years and 65 years or above years, sex, smoking habit, and presence or absence of diabetes mellitus, atrial fibrillation, and dyslipidemia. But hypertension and ischemic heart disease (IHD) were significantly associated with circadian variation of stroke. The occurrence of ischemic stroke and hemorrhagic stroke was most common from 6 am to 12 pm (47.5% and 48.1%) respectively. When considered separately, significant circadian variation noted for ischemic stroke and hemorrhagic strokes were also noted. Conclusions: The study contributes further evidence for the circadian variation in the occurrence of ischemic stroke and hemorrhagic stroke. Attempts to prevent their occurrence must take into account this circadian variation.